2019
DOI: 10.1177/1086296x19833783
|View full text |Cite
|
Sign up to set email alerts
|

Constructs of Teaching Writing in Research About Literacy Teacher Education

Abstract: This review of empirical research focused on the preparation of writing teachers synthesizes findings from 82 articles published between 2000 and early 2018. The new understandings generated through this analysis are presented in two sections. First, we provide an overview of how the studies we reviewed draw from and circulate dominant discourses of writing, leading to a call for more transparency and clarity on the part of scholars who study writing and writing pedagogy. Then, we explore experiences in litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 55 publications
(68 reference statements)
1
8
0
Order By: Relevance
“…Today's literacy is more complex, not only understanding text, language, and language skills, but more than that. Today's literacy includes all activities or daily activities (Bomer et al, 2019). Literacy based on Pancasila dan citizenship education learning contains literacy components.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Today's literacy is more complex, not only understanding text, language, and language skills, but more than that. Today's literacy includes all activities or daily activities (Bomer et al, 2019). Literacy based on Pancasila dan citizenship education learning contains literacy components.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, literacy-based learning, especially in Civics subjects, is now more complex, not only related to reading and writing. This is according to the theory put forward by Bomer et al (2019) argues that today's literacy is more complex, not only understanding text, language, and language skills, but more than that, today's literacy includes all daily activities or activities. The implementation of literacy culture in Senior High Schools in Bantul Regency, Yogyakarta includes: (1) extracurricular activities include scouting, journalism, religion, sports, and information technology.…”
Section: Pancasila and Citizenship Education Learning Based On Literacy Model At Senior High Schools In Bantul Regencymentioning
confidence: 99%
“…In their synthesis, Bomer, Land, Rubin, and Van Dike (2019) found that studies promoting process and social practice discourses related to writing were present in their data set, although often discourses that promote skills‐based instruction remain prevalent in the field. Similarly, the authors found that no one activity supported the interruption of traditional notions of writing and writing instruction held by preservice teachers.…”
Section: Research On Literacy Teacher Preparationmentioning
confidence: 99%
“…There are still, however, areas that need attention. For example, how reading, writing, and/or literacy were defined in the research was not always clearly articulated; as a result, it seemed that traditional notions of reading versus writing are still prominent (see Bomer et al, 2019; Hikida et al, 2019). Similarly, much of the research in these syntheses looked at preservice teacher preparation in a single semester and in one context, rather than across time and space (see Fowler‐Amato, LeeKeenan, et al, 2019; Hoffman et al, 2019).…”
Section: Research On Literacy Teacher Preparationmentioning
confidence: 99%
“…Process discourse refers to both mental processes that constitute the writing act and practical processes of producing a written product (i.e., planning, drafting, revising). Within this discourse, people get better at the processes of writing by practicing them (Bomer, Land, Rubin & Dike 2019).…”
Section: Introductionmentioning
confidence: 99%